Making the metropolitan landscape [ standing firm on middle ground - Stauber, Jennifer; Tatom, Jacqueline (Routledge, 2009)
Argues for a progressive design practice which speaks to the complexity and diversity of American cities. Recognizing that the landscape of the American city has reflected democratic aspirations, mixed cultural heritage, and practical necessity, this book proposes various frameworks for describing and interpreting metropolitan landscape